2020
DOI: 10.5114/pjr.2020.102194
|View full text |Cite
|
Sign up to set email alerts
|

The risk of renal function deterioration in abdominal aortic stent graft patients with and without previous kidney function failure – an analysis of risk factors

Abstract: Purpose: Kidney failure influences the treatment outcomes of abdominal aortic aneurysm (AAA). A prospective study of renal function before and after aortic stent-graft treatment was performed. Special attention was paid to the influence of preoperative kidney function as well as the impact of the radiological follow-up. Material and methods:A total of 214 endovascularly treated AAA patients were included. In all cases, pre-and postoperative estimated glomerular filtration rate (eGFR) and serum creatinine were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(38 reference statements)
0
2
1
Order By: Relevance
“…15 However, in another cohort including 214 patients treated with EVAR, no correlation was found between CM volume and the final eGFR. 20 In our cohort, we did not find a significant difference in the amount of CM used between the patients who developed CI-AKI and those who did not (90.0 vs 84 mL, P = .583). This may be partly explained by an “as low as reasonably achievable” approach in our center.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…15 However, in another cohort including 214 patients treated with EVAR, no correlation was found between CM volume and the final eGFR. 20 In our cohort, we did not find a significant difference in the amount of CM used between the patients who developed CI-AKI and those who did not (90.0 vs 84 mL, P = .583). This may be partly explained by an “as low as reasonably achievable” approach in our center.…”
Section: Discussioncontrasting
confidence: 53%
“…12,13 Previous studies reported an incidence of CI-AKI in patients undergoing EVAR between 6.9 and 28%. 12,[14][15][16][17][18][19][20] In the present cohort of 102 patients, we report for the first time, the incidence of CI-AKI specifically in patients who underwent ch-EVAR, with a rate of 13.7%, which is within the low range compared with other EVAR procedures. In our center, we applied an "as low as reasonably achievable" approach and the median of CM used was low (85 mL), which could partly explain a relatively low rate of incidence of CI-AKI.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Also, in the case of a more extensive dissection, kidneys adjust to a physiologically abnormal level of perfusion. Therefore, recovering a physiologically typical flow split after surgery may lead to the deterioration of renal function [75]. Additionally, due to the added aortic compliance introduced by the use of a compliant graft, EL decreased by 4% in the BC1 case compared to the baseline.…”
Section: Energy Lossmentioning
confidence: 99%